Tipologi Pesantren: Salaf dan Kholaf - Hayati, Nur (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2019)
Pesantren is a traditional institution that maintains the old system while using a new system capable of answering the today’s challenges. Pesantren is not the stagnant institution that we used to know with a less advanced institution. Currently, Pesantren exceeds the other exist institutions because their output really expected the community to be able to give examples and become role models in the community. In this case, Pesantren is not a museum that can only be seen and remembered in history. However, it is able to breaking down the old history and giving new insight to an institutional system, life and safety and shared comfort. There are two terms in the pesantren’s typology. First, Pesantren Salaf that still teaches classical Islamic books as the core of his education. The application of the Madrasah system is used to facilitate the Sorogan system that used in the old form institutes, without introducing general knowledge. Secondly, Pesantren Kholaf, teach general knowledge in developed Madrasah or establish the types of public schools in the areas of the Pesanten.